Ventilatory mechanics and expiratory flow limitation during exercise in patients with obstructive lung disease - Potter, William A. (1971)
The interrelationships among transpulmonary pressure, flow, and volume during exhausting exercise were studied in 12 males with chronic obstructive lung disease. Expiratory pressure during exercise was compared with flow-limiting pressure (P(max)) measured at rest. In 11 patients, expiratory pressure during exercise exceeded P(max), indicating that ventilation became mechanically inefficient. P(max) values of the patients were lower than those of normal subjects. Evidence of expiratory flow augmentation during exercise was noted in two subjects. Since 10 subjects achieved maximal expiratory flow predicted from flow-volume curves when heart rate was not maximal, we conclude that exercise capacity in most subjects was clearly limited by the deranged ventilatory apparatus. Elevations in mean intrathoracic pressure during exercise also may interfere with venous return and impose an additional limitation.